GPCR activation: protonation and membrane potential - Zhang, Xuejun C. (Protein Cell, 2013)
GPCR proteins represent the largest family of signaling membrane proteins in eukaryotic cells. Their importance to basic cell biology, human diseases, and pharmaceutical interventions is well established. Many crystal structures of GPCR proteins have been reported in both active and inactive conformations. These data indicate that agonist binding alone is not sufficient to trigger the conformational change of GPCRs necessary for binding of downstream G-proteins, yet other essential factors remain elusive. Based on analysis of available GPCR crystal structures, we identified a potential conformational switch around the conserved Asp2.50, which consistently shows distinct conformations between inactive and active states. Combining the structural information with the current literature, we propose an energy-coupling mechanism, in which the interaction between a charge change of the GPCR protein and the membrane potential of the living cell plays a key role for GPCR activation.